2015
DOI: 10.5312/wjo.v6.i6.449
|View full text |Cite
|
Sign up to set email alerts
|

Bone graft substitutes for spine fusion: A brief review

Abstract: Bone graft substitutes are widely used in the field of orthopedics and are extensively used to promote vertebral fusion. Fusion is the most common technique in spine surgery and is used to treat morbidities and relieve discomfort. Allograft and autograft bone substitutes are currently the most commonly used bone grafts to promote fusion. These approaches pose limitations and present complications to the patient. Numerous alternative bone graft substitutes are on the market or have been developed and proposed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 82 publications
0
57
0
3
Order By: Relevance
“…Osteoconduction maintains the balance of new bone growth by replacing the bone graft present and incorporating the new bone growth with the adjacent host bone that leads to union of the central zone of fusion. 6 Finally, remodeling results in thickening of the cortical rim at the margins of the fusion adding to the structural integrity.…”
Section: Bone Grafts and Fusionmentioning
confidence: 99%
“…Osteoconduction maintains the balance of new bone growth by replacing the bone graft present and incorporating the new bone growth with the adjacent host bone that leads to union of the central zone of fusion. 6 Finally, remodeling results in thickening of the cortical rim at the margins of the fusion adding to the structural integrity.…”
Section: Bone Grafts and Fusionmentioning
confidence: 99%
“…Moreover, rhBMP-2 also demonstrated as an enhancer of bone healing in a rat femoral bone defect model and a rabbit ulna osteotomy model by delivering rhBMP-2 using a carrier such as calcium phosphate or liposome [67,68]. More clinical studies have shown the utilization of rhBMP-2 as a complete bone graft replacement in spinal fusion surgery [69,70] and several studies have demonstrated that the induction efficacy of BMP-2 in fusion is much way better than autogenous bone graft [69,71], and very useful in intervertebral and lumbar posterolateral fusion [72]. In dentistry, BMP-2 also can induce the formation of new dentine, plus has likely to be a substitute for root canal surgery and a very effective bone inducer for periodontal reconstructive implantation [73].…”
Section: Bmp-2 As Potential Diseases and Cancer Therapiesmentioning
confidence: 99%
“…En una reciente revisión sistemática de sustitutivos óseos en osteotomías de apertura de tibia se comprueba que la consolidación ósea se obtiene antes con el uso de autoinjertos que con homoinjertos, que a su vez tienen mejores tasas de unión que los compuestos sintéticos (25) . Y en otra realizada en fusión espinal (26) se apoya que, aunque muchos sustitutivos óseos funcionan bien como osteoconductores, solo la BMP-2 y la BMP-7 proporcionan evidencia de uso para utilizarlos como osteoinductores. Los hidrogeles de ingeniería tisular, los compuestos poliméricos sintéticos y la terapia génica vírica también tendrían potencial de uso en fusión vertebral, pero se necesita una mayor investigación para poder utilizarlos en la práctica clínica (26) .…”
Section: Evidencias Actuales De Los Sustitutivos óSeosunclassified
“…Y en otra realizada en fusión espinal (26) se apoya que, aunque muchos sustitutivos óseos funcionan bien como osteoconductores, solo la BMP-2 y la BMP-7 proporcionan evidencia de uso para utilizarlos como osteoinductores. Los hidrogeles de ingeniería tisular, los compuestos poliméricos sintéticos y la terapia génica vírica también tendrían potencial de uso en fusión vertebral, pero se necesita una mayor investigación para poder utilizarlos en la práctica clínica (26) . En otra revisión de fracturas osteoporóticas, Lieshout y Alt (16) concluyen que es decepcionante observar que existen muy pocos datos en relación con los sustitutivos óseos y BMP, que no permiten realizar un algoritmo basado en la evidencia en esta patología, por lo que animan a los investigadores a centrarse en estos materiales y su uso en fracturas osteoporóticas.…”
Section: Evidencias Actuales De Los Sustitutivos óSeosunclassified